The Occurance of Fall Army Worm (Spodoptera frugiperda) (Lepidoptera: Noctuidae) and the Level of Damage on Corn (Zea mays) Plantations In Several Locations in Ambon Island - Eli Desta Girsang; J A Leatemia; M R Uluputty (Agrologia, 2022)
Spodoptera frugiperda is an invasive insect pest that introduced to Indonesia in 2019. This study aims to determine the spread of S. frugiperda, as well as the level of damage (plant damage intensity) on corn plantations owned by farmers in several locations in Ambon Island. The research was conducted in six locations, namely Tawiri Village, Taeno Hamlet, Poka Village, Karang-Karang Hamlet, Passo Village and Liang Village. This study used a survey method by direct observation of corn plantations owned by farmers and interviews with farmers. Observations were made when the corn plants were about one month after planting. The results showed that there were S. frugiperda at the six research sites with the highest level of damage was in Taeno hamlet with a damage intensity of 40.94% (moderate category) and an attack area of 90%; while the lowest level of damage was in Karang-Karang Hamlet with an intensity of damage of 7.42% (light category) and an attack area of 30%.